Unravelled: why awareness-raising strategies fail to increase women’s political ambitions - Antonetti, M (2023)
In Western society, women are still socialised to manifest lower interest in political leadership roles compared to men (Lawless & Fox, 2010). Awareness-raising strategies are essential to combat the negative repercussions of a gendered political socialisation and increase diversity in political representation (Krook & Norris, 2014). Nevertheless, most of these strategies seem unfit to affect the political ambitions (i.e. interest for seeking political office) of women in the general population (Foos & Gilardi, 2020; Pruysers & Blais, 2018; 2019). This monograph aims to understand why these tools fail to produce desired results.